IoT Challenges and Issues: A Comprehensive Review of Software Defined Networking and Network Function Virtualization Solutions - Zerifi, Manare; Ezzouhairi, Abdellatif; Boulaalam, Abdelhak; Baghrous, Mohamed (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The idea behind the Internet of Things (IoT) is to connect everything, including laptops, smartphones, sensors, and other devices, to the Internet. To build an autonomous environment without human intervention. This novel network was used in several industries, including smart homes, smart cities, healthcare, etc. For this reason, IoT networks are growing in infrastructure. As a result, the administration of this vast array of linked devices and produced data becomes more complicated. Thus, a new elastic mechanism is required for this dynamic and rapid evolution in configuration, control, management, etc. Network Function Virtualization (NFV) and Software Defined Networking (SDN) have become essential points in scientific research to overcome IoT challenges such as security, heterogeneity, energy efficiency, interoperability, and more. These two approaches have proven their efficiency in adapting to dynamic and evolving networks. SDN reduces network latency by up to 30% and increases device scalability by 40%. At the same time, NFV optimizes resource allocation, achieving up to a 35% reduction in energy consumption and a 20% decrease in operational costs through virtualized infrastructure. In this review, we systematically analyze solutions designed for IoT systems by developing a state-of-the-art for NFV and SDN and thoroughly researching the various problems that IoT will face. Thus, we compare SDN- and NFV-based IoT solutions to overcome these challenges. Lastly, we will discuss the different obstacles that can lower the performance of SDN/NFV applications on the IoT. The contribution of this review lies in its systematic evaluation and comparison of current NFV and SDN approaches, providing valuable insights and paving the way for future research to enhance the integration and management of IoT systems.